2006
DOI: 10.1080/14017430600746268
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of atrial fibrillation in stable symptomatic coronary disease

Abstract: The presence of AF in patients with stable symptomatic CAD is an independent risk factor and in particular in the first 30 days for subsequent mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
3
26
0
2
Order By: Relevance
“…In any event, in patients presenting with persistent signs of impaired LV dysfunction, coronary angiography and careful consideration about the underlying heart disease is recommended ([20] page 11). Ischemic cardiomyopathy, heart failure and neurohumoral activation are hypothesized to play an important mediating role in the development of new AF [5], [13] and previous studies have demonstrated the occurrence of AF in congestive heart failure and in myocardial infarction [26]. We agree with Movahed et al [22] that it is possible that coronary microvascular disease with ischemia (inducing metabolic stress) could be involved in the development of AF.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In any event, in patients presenting with persistent signs of impaired LV dysfunction, coronary angiography and careful consideration about the underlying heart disease is recommended ([20] page 11). Ischemic cardiomyopathy, heart failure and neurohumoral activation are hypothesized to play an important mediating role in the development of new AF [5], [13] and previous studies have demonstrated the occurrence of AF in congestive heart failure and in myocardial infarction [26]. We agree with Movahed et al [22] that it is possible that coronary microvascular disease with ischemia (inducing metabolic stress) could be involved in the development of AF.…”
Section: Discussionsupporting
confidence: 81%
“…The Framingham study suggested that angina predisposed to AF and that the association of AF with CAD was stronger in men [7]. Despite the high prevalence of CAD in patients with AF of 18–46.5% [8]–[12], the prevalence of AF among patients with proven CAD is extremely low, at 0.2–5% [13]–[16]. By contrast, a survey of historic literature by Zipes indicates that AF commonly occurs in patients with CAD [17].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AF in this unselected patient population undergoing PCI with the unrestricted use of DES amounted to 5.3%, which is consistent with previous reports of patients with stable CAD and acute MI [2][3][4][5][6][7] . In line with established risk factors for AF 8,9 , patients with AF were older and had a higher prevalence of hypertension and compromised left ventricular ejection fraction.…”
Section: Discussionsupporting
confidence: 78%
“…CAD and AF coexist in up to 25% of patients with stable CAD or acute myocardial infarction (MI) [2][3][4][5][6][7] , which may be related to common risk factors including advanced age, diabetes, hypertension, and congestive heart failure 8,9 . Apart from cerebrovascular events, AF has been associated with a one-and-a-half to twofold increased risk of mortality in the general population after adjustment for pre-existing cardiovascular conditions 8 as well as adverse in-hospital and long-term outcome after MI 4,10 .…”
mentioning
confidence: 99%
“…В исследовании, выполненном S. Kralev et al, у 13% пациентов с ФП, подвергшихся коронаро-графии, диагностированы гемодинамически значимые стенозы коронарных артерий, а час-тота постоянной формы аритмии была практи-чески идентичной в обеих группах -с ИБС и без нее (30 и 27% соответственно) [11]. В свою оче-редь, частота сопутствующей ФП среди больных ИБС составляет всего лишь в 0,2-5% [12].…”
Section: Introductionunclassified